Does consistency with detailed national data matter for calculating carbon footprints with global multi-regional input-output tables? A comparative analysis for Belgium based on a structural decomposition - Caroline Hambÿe; Bart Hertveldt; Bernhard Michel (Journal of Economic Structures, 2018)
Consistency with detailed national data is an important challenge when using multi-regional input-output (MRIO) tables for carbon footprint analysis at the national level. This article presents carbon footprint calculations for Belgium with original and adapted MRIO tables from the World Input-Output Database (WIOD) project. For constructing the adapted tables, we have reproduced the MRIO construction process of WIOD replacing source data for Belgium by detailed supply-and-use table data from national sources and keeping these unchanged in the balancing phase. The novelty of our approach is that we investigate a time series and analyse the differences in results with respect to the original tables using structural decomposition analysis (SDA). According to our calculations, Belgium's carbon footprint is up to 15% lower than in calculations based on the original WIOD MRIO tables. The SDA reveals that this is largely due to differences in data on import uses and taxes and subsidies. Hence, consistency with detailed national data does indeed matter for MRIO-based carbon footprint calculations. Therefore, we advocate building global MRIO tables by incorporating a maximum of detailed national data in close cooperation with national statistical institutes before letting the balancing process work freely.
Keywords: 330; Carbon footprint; Global multi-regional input-output tables; National accounts consistency; Consumption-based emission accounting; Structural decomposition analysis